2017
DOI: 10.1007/s13193-017-0700-z
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Factors Affecting the Longevity of Voice Prosthesis Following Total Laryngectomy with a Review of Literature

Abstract: Tracheoesophageal voice puncture (TEP) coupled with the use of voice prosthesis has been considered as the gold standard for speech rehabilitation in patients of advanced laryngeal/hypopharyngeal carcinomas, who have undergone a total laryngectomy with or without partial pharyngectomy. Although prosthetic voice rehabilitation is commonly practiced worldwide including India, there is a paucity of published Indian data, more so in the current era of organ conservation. This study included 60 laryngectomized pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
1
8

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 47 publications
0
20
1
8
Order By: Relevance
“…Airflow through the esophageal structure will generate a new fundamental tone that, as with the esophageal voice, will later be converted into speech sounds. The use of a voice prosthesis for communication requires daily maintenance and needs to be replaced approximately every 6 months, (130)(131)(132) The rate of complications can range from 15 to 72% (132), being the most frequent the leak through de voice prosthesis and the leak around the tracheoesophageal prosthesis.…”
Section: -Tracheoesophageal Speech (Voice Prosthesis)mentioning
confidence: 99%
“…Airflow through the esophageal structure will generate a new fundamental tone that, as with the esophageal voice, will later be converted into speech sounds. The use of a voice prosthesis for communication requires daily maintenance and needs to be replaced approximately every 6 months, (130)(131)(132) The rate of complications can range from 15 to 72% (132), being the most frequent the leak through de voice prosthesis and the leak around the tracheoesophageal prosthesis.…”
Section: -Tracheoesophageal Speech (Voice Prosthesis)mentioning
confidence: 99%
“…Device lifetime in our study was similar to other studies, which report a mean device lifetime between 2 and 14 months. 5,11,21,34,35 Bozec et al reported a median device lifetime of 7.6 months (ranging from 1.2 to 39.5 months).…”
Section: Device Lifetimementioning
confidence: 99%
“…Regarding the article by Krishnamurthy et al on 60 laryngectomized patients with prosthetic voice rehabilitation (Mar. 9 issue) [1], 82% of patients preserve successful tracheaesophageal speech. These data agree with the existing literature [2].…”
Section: Letter To Editormentioning
confidence: 99%